2011
DOI: 10.1016/j.childyouth.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Children's subjective well-being: International comparative perspectives

Abstract: We are enjoined by the United Nations Convention on the Rights of the Child to take account of the views of children. One way this can be done is by asking children about their lives in sample surveys. This paper is a comparison of the results obtained to sample survey questions on subjective well-being of children at two contrasting levels of analysis-international macro (European Union 29) and national level micro (England). At both levels, children"s well-being is accessed in terms of three subjective domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
2
23

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 13 publications
4
81
2
23
Order By: Relevance
“…LS is associated both with physical and mental health in children and adolescents as well as with the various health behaviours among them (5)(6)(7)(8)(9). Studies have also demonstrated that LS is related to age, gender, material and housing circumstances, family and school environment, and socioeconomic status (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…LS is associated both with physical and mental health in children and adolescents as well as with the various health behaviours among them (5)(6)(7)(8)(9). Studies have also demonstrated that LS is related to age, gender, material and housing circumstances, family and school environment, and socioeconomic status (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 98%
“…Studies have also demonstrated that LS is related to age, gender, material and housing circumstances, family and school environment, and socioeconomic status (6)(7)(8)(9)(10)(11)(12)(13). Furthermore, LS in adolescents is strongly influenced by life experiences, social relationships, stress and anxiety, social competence and good coping skills, self-esteem, self-acceptance, the ability to love oneself, optimism, and individual spirituality (7,8,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…According to UNICEF (2011), advancing adolescents' development requires keen understandings of their current circumstances, and adolescents should be encouraged to contribute as integral partners with adults in health-related decisions. While recent research and educational theory in the field underline taking children's views into consideration to advance knowledge about their well-being and happiness (Awartani et al 2008;Bradshaw et al 2011;Noddings 2003), adolescents' voices are rarely heeded, counter to the guidelines in the Convention on the Rights of the Child (UNICEF 2011).…”
Section: Introductionmentioning
confidence: 98%
“…LS is positively related to mental and physical health as well as health behaviors in adolescents. LS is furthermore associated with material and housing circumstances, and negatively related to risk behaviors like substance use or violent behaviors (Park 2004;Bradshaw et al 2011).…”
Section: Introductionmentioning
confidence: 99%